Impact of Photovoltaics Power Plant Penetration on a Closed-Loop Distribution Network's Power Quality Indices - Klajdi Kamberi; Donard Shaliu; Marialis Çelo; Andi Hida; Viktor Rrotani (Journal of Sustainable Development of Energy, Water and Environment Systems)

(untitled)
The integration of high levels of photovoltaic power plants into existing networks in recent years has brought significant opportunities in terms of greenhouse gas reduction, help to increase the security of supply, and creating new job options as well as challenges for power systems regarding the power quality. In this research work the power quality in a closed-loop distribution system which is a particular type of operation of distribution feeders, under the condition of large-scale penetration of photovoltaics is well investigated. Exploring different operation scenarios helps in understanding the complexities and impacts of integrating photovoltaic power plants for two different operation scenarios of the system, based on the minimum and maximum load during the day. These scenarios are interlocked each into considering three variants of integrability: the connection of photovoltaic power plants in the low voltage nodes, in the medium voltage nodes and on both sides. Accommodations of the above scenarios renders in designing action policies to manage and optimize the integration of PV power plants, securing reliable and efficient quality power delivery. The chosen connection strategies of the tested photovoltaic system lead to many benefits, such as reduction of the network power losses, decrease in the number of overloaded transformers and an increase in voltage levels among the nodes, but without exceeding the rated values. The only parameter that exceeds the permissible limits in all studied scenarios is the total harmonic distortion level of the voltage, which can be easily addressed by applying mitigations strategies (filter applications, better management and optimal placing of photovoltaics). As a conclusion the outputs of these study are a good starting point for extended research in the way toward a smooth, qualitative and cost-effective large-scale integration of photovoltaics into the existing power system in Albania.